Does Therapeutic Zinc Level of Supplementation for Diminutions of Acute Diarrheal Morbidity Varied in Public and Private Health Institutions in Ethiopia, Data from EDHS 2016? - Fassikaw Kebede; Merkineh Markos (Hindawi Limited, 2022)
Background. Supplementation of zinc is a therapeutic medication for under-five children diminution incidence, severity, duration, and intensity of acute diarrhea morbidity. Nevertheless, levels of therapeutic zinc supplementation varied across public and private health institutions in Ethiopia. Thus, this study was aimed at estimating the levels of therapeutic zinc supplementation and factors associated for intent to be utilized among caregivers with their dyads, data from Ethiopia Demographic and Health Survey (EDHS 2016). Methods. The data used were from a secondary analysis of the Ethiopia Demographic and Health Survey in 2016 (EDHS). Overall, 1090 under-five children with acute diarrheal cases of two weeks before the EDHS 2016 were included. After cleaning, editing, and coding variables, the result was presented with frequency, tables, and graphs. Bivariable and multivariable logistic regression was conducted to identify and determine factors associated after zinc is prescribed for utilizations by caregivers. Result. The mean (±SD) age of participant children was found to be 36.4(±7.07) month. The overall levels of therapeutic zinc supplementation were 38.7% (95% CI: 35.8, 41.6) in public (29.08%) and private 138 (12.66%), respectively. The prescribed therapeutic zinc was influenced for utilization through maternal educational status (AOR=2.55; 95% CI: 1.95, 3.47; P=0.001), availability of health insurance (AOR=10.7; 95% CI: 7.2, 16; P=0.001), media exposure status (AOR=2.1; 95% CI: 1.7, 3.6; P=0.001). Conclusion. More than twofold time therapeutic zinc was prescribed in public than in private health institutions. Health care workers should be encouraged both in public and private health institutions for zinc prescription.